Stability analysis of a predator-prey model with piecewise constant argument of generalized type using Lyapunov functions - Aruğaslan, D.; Özer, A. (Нелінійні коливання, 2013)
In this study, we consider a Lotka – Volterra type predator-prey model with piecewise constant arguments of generalized type and investigate the stability of the positive equilibrium point of the proposed model. Although the model includes piecewise constant delays, we do not use Lyapunov functionals. We establish the stability conditions using Lyapunov functions of the corresponding model of ordinary differential equations. In order to illustrate the validity of our results, we present an appropriate example and numerical simulations. Розглянуто модель «хижак-жертва» типу Лотки – Вольтерра iз кусково-сталими аргументами та вивчено стiйкiсть додатного положення рiвноваги розглядуваної моделi. Незважаючи на те, що модель має кусково-сталi запiзнення, функцiонали Ляпунова не використовуються. Отримано умови стiйкостi з використанням функцiй Ляпунова для вiдповiдної моделi звичайних диференцiальних рiвнянь. Для iлюстрацiї отриманих результатiв наведено вiдповiдний приклад та числовi розрахунки.